Paixão, mito e formas de vida em textos publicitários - Nascimento, Edna Maria Fernandes dos Santos [UNESP] (Universidade Estadual de Londrina, 2014)
The passion, understood by Aristotle, as a contingency which causes a change in the essence of the subject, was object of research of the Greek philosopher as rhetorical strategy used by the speaker to touch its listeners. The greimasian semiotics, enlarging the concept of Aristotle’s passion, understands it as the soul states of a subject that can be gathered form the analysis of a text. Reflections towards the passion discursivization and its persuasion effects in advertisements lead us to establish the relationships between passion, myth and ways of life.

A paixão, concebida por Aristóteles como uma contingência que provoca mudança na essência do sujeito, foi objeto de estudo do filósofo grego como uma estratégia retórica utilizada pelo orador para comover seu auditório. A semiótica greimasiana, ampliando o conceito de paixão aristotélica, a concebe como estados de alma de um sujeito que podem ser depreendidos a partir da análise de um texto. Reflexões sobre a discursivização das paixões e sobre seus efeitos de persuasão em textos publicitários conduzem-nos a estabelecer relações entre paixão, mito e formas de vida.
Passion, myth and ways of life in advertising
Keywords: Advertisements; Passion; Ways of life; Texto publicitário; Paixão; Formas de vida